THE STRUCTURE GEOLOGY MODELING OF ULUBELU GEOTHERMAL FIELD HEAT SOURCE USING GRAVITY - Damayanti, Chairunnisa
Global warming is one of the problems that the world facing currently. One of the reasons is the use of hydrocarbon fuels from organic materials. There needs alternative energy that is harmless to nature to reduce this impact. Geothermal energy is one of clean energy and harmless to nature because it has low carbon emissions. Geothermal energy is sourced from heat that comes from within the earth. Geothermal is closely related to volcanism. Indonesia located in seismic lines called the “ring of fire”, this situation provides benefits for Indonesia because it makes Indonesia have a large geothermal potential. Prospective geothermal fields can be determined by identifying heat sources in subsurface structures. One of the heat sources in geothermal system is from igneous rock intrusion. The used method is gravity method, a method that utilizes anomalies below the surface density. The difference density of subsurface can explain the presence of intrusion. One of the geothermal fields that are already operating in Indonesia is the Ulubelu Geothermal Field, located in Province Lampung, so the existence of igneous rock intrusion needs to be identification. This research aims to make 2.5D forward modeling of heat source in Ulubelu geothermal. The data used is the 1991 Kotaagung Complete Bouger Anomaly Sheet Map. The initial stage of this research is determining the study area, which is the area around the Ulubelu Geothermal Field. The selected area is digitized to create a digital map, then the map is processed using the moving average method to separate regional and residual anomalies. Forward modeling utilizes the Residual Bouger Anomaly Map and the geological information of the study area so the output can correlate with the actual condition as best as possible. The results of processing from Northwest-Southeast oriented cross-section there is a high anomaly in Southeast suspected as a heat source area of geothermal system Ulubelu.